Spatial abilities of medical graduates and choice of residency programs. Issue 2 (20th June 2014) - Langlois, Jean; Wells, George A.; Lecourtois, Marc; Bergeron, Germain; Yetisir, Elizabeth; Martin, Marcel
<x xml:space="preserve">Abstract</x> Spatial abilities have been related in previous studies to three‐dimensional (3D) anatomy knowledge and the performance in technical skills. The objective of this study was to relate spatial abilities to residency programs with different levels of content of 3D anatomy knowledge and technical skills. The hypothesis was that the choice of residency program is related to spatial abilities. A cohort of 210 medical graduates was enrolled in a prospective study in a 5‐year experiment. Spatial abilities were measured with a redrawn Vandenberg and Kuse Mental Rotations Test (MRT) in two (MRTA) and three (MRTC) dimensions. Medical graduates were enrolled in Family Medicine (n = 76, 36.2%), Internal Medicine (64, 30.5%), Surgery (52, 24.8%), and Anesthesia (18, 8.6%). The assumption was that the level of 3D anatomy knowledge and technical skills content was higher in Surgery and Anesthesia compared to Family Medicine and Internal Medicine. Mean MRTA score of 12.4 (±SD 4.6), 12.0 (±4.3), 14.1 (±4.3), and 14.6 (±4.0) was obtained in Family Medicine, Internal Medicine, Surgery, and Anesthesia, respectively (P = 0.0176). Similarly, mean MRTC score of 8.0 (±4.4), 7.5 (±3.6), 8.5 (±3.9), and 7.9 (±4.1) was obtained (P = 0.5647). Although there was a tendency for lower MRTA score in Family Medicine and Internal Medicine compared to Surgery and Anesthesia, no statistically significant main effect of residency, year, sex, or the interactions were observed for the MRTA and MRTC. Studied sample of medical graduates was not found to choose their residency programs based on their innate spatial abilities. Anat Sci Educ 8: 111–119. © 2014 American Association of Anatomists.